Tahlilan dan Tawasul (Perspektif KH. Misbah Al-Musthafa dalam Tafsir Al-Iklil fi Ma’ani Al-Tanzil) - Sabella, Dina; Rahmawati, Emma (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: This research aims to examine views of KH. Misbah Al-Musthafa, a renowned scholar in Java who discusses the practices of tahlilan and tawassul in his Quranic tafsir entitled Al-Iklil fī Ma’ani Al-Tanzil. The study employs a qualitative method with a literature review, with the primary source being the Quranic tafsir entitled Al-Iklil fī Ma’ani Al-Tanzil by KH. Misbah Al-Mushtafa. Data was collected through the identification and analysis of texts related to tahlilan and tawassul in the aforementioned book. Additionally, other relevant references such as books, journals, and articles were used to support the analysis. In the interpretation of Al-Iklil fī Ma’ani Al-Tanzil, KH. Misbah Al-Musthafa provides a deep understanding of these two practices. He attempts to analyze the Quranic and hadith evidence related to tahlilan and tawassul, and provides a comprehensive interpretation based on the understanding of the Quran and Sunnah. The conclusion of this research is that KH. Misbah Al-Musthafa views tahlilan and tawassul as religious practices that have legitimacy in the Javanese Islamic tradition, but they must be based on a correct theological understanding and carried out in accordance with the teachings of the religion.